The Problem of Value Neutrality of Science in the 20th Century Philosophy (Max Weber, Analytical Philosophy of Science and Metathics, Critical Theory) - Norkus, Zenonas (Problemos, 2001)
The article analyses prehistory of current discussions on the problem of value neutrality of science. In this problem, three aspects are distinguished: logical one (represented by the dichotomy of descriptive and evaluative statements, and by “Hume’s principle”); methodological one (demand to base acceptance and rejection of hypotheses on cognitive values only), and ethical one (prohibition to advocate and to promote non-cognitive values on behalf of science). Three stages in the ongoing philosophical discussions on value neutrality of science are distinguished. The scope of article is restricted, however, to analysis of arguments propounded and discussed during the first two stages. Special consideration is paid to difficulties confronted by the proponents of this principle. One of these difficulties is dependence of choice of significance level in statistical inference on practical considerations concerning consequences of the type I vs. type II error (this is a problem for logical empiricist philosophy of science). Another one is relevant for assessment of critical rationalism: is dichotomy of decisions and facts compatible with thesis of conventionality of “basic statements”, i.e., their dependence on decisions? Reasons for principled opposition to the idea of value neutral science by “critical theory” are discussed locating these reasons in the peculiarities of its self-understanding as critical social science with emancipatory mission. The classical formulation of value neutrality of science by German sociologist Max Weber (1864-1920) is used as the starting point in exposition and comparison of different formulations of this principle. A special attention is paid to Weber’s statement that “sciences of culture” have value presuppositions which time to time undergo a radical change (this thesis is most strongly stated in Weber’s astronomic metaphor of constellation change in “Objektivität” article). This statement is considered as anticipation of ideas current in postpositivist philosophy of science that epistemic values (aims of science) are historically changeable. The question is inquired what place Weber’s views concerning possibility of rational discussion about “ultimate valuations” occupy among the metaethical standpoints established in the post-Weberian analytical metaethics? Against the prevailing interpretations of Weber as noncognitivist of emotivist (Macintyre) or prescriptivist (Runciman) a kind suggestion is made that Weber’s views can be considered as cognitivist (namely, as cognitivist antinaturalist scepticism or agnosticism). As a prototype for Weber’s concept of conflict between the “ultimate” valuations is considered Kant’s transcendental dialectics of pure (theoretical reason). So Weber’s concept is interpreted as outline of quasitranscendental dialectics of practical reason. This dialectics (like that of teoretical reason as analyzed by Kant) doesn’t contain the statement that “ultimate” value statements (Weber) or metaphysical statements (Kant) have no truth value. It only contains the thesis of epistemic unaccessibility of practical (Weber) or metapysical (Kant) truth for human understanding, i.e., scepticism or agnosticism about the knowledge of “ultimate” values (Weber) or “things in themselves” (Kant)
Keywords: value neutrality of science; Max Weber; metaethics; critical rationalism; critical theory